Atlas of Breast Tomosynthesis : Imaging Findings and Image-Guided Interventions - Sonnenschein, Martin; Waldherr, Christian (Springer International Publishing : Imprint: Springer, 2017)
This superbly illustrated atlas of breast tomosynthesis covers all aspects and applications of the technology, which reduces tissue overlap and facilitates the recognition of small cancers. After clear explanation of basic principles of the technique, individual chapters address diagnostic criteria, indications, and use of breast tomosynthesis as a screening tool. The findings obtained in the full range of benign and malignant conditions, including postoperative changes, are then presented with the aid of a wealth of high-quality illustrations from case examples. Detailed attention is paid to the BI-RADS classification, bearing in mind the ability of tomosynthesis to reduce categorizations as BI-RADS 3 and 0, thereby decreasing the recall rate. The book concludes by examining tomosynthesis-guided interventions such as vacuum-assisted breast biopsy and galactography.- Resumé vydavatel